Leveraging innate immune signals in CD8+ T cells to boost antitumor immunity - Albert, Gabriella K.; Cao, Phoebe; Davila, Eduardo (Frontiers in Immunology, 2025)
Pattern recognition receptors (PRRs), traditionally characterized in innate immune cells, are emerging as critical modulators of T cell function. Toll-like receptors (TLRs), STING, RIG-I-like receptors (RLRs), and natural killer receptors (NKRs) are expressed by CD8+ T cells, where they influence various cellular responses. Primarily serving as noncanonical costimulatory signals, TLRs can modulate T cell activation, differentiation, metabolic fitness, and memory formation. RLRs and STING can promote T cell expansion and cytokine production. Both activating and inhibitory NKRs can also alter T cell cytotoxicity and differentiation. As demonstrated in recent advancements, the capacity of these signaling cascades to enhance T cell responses offers promising therapeutic opportunities in cancer. Clinical strategies are being developed to selectively harness each of these pathways, such as TLR and STING agonists to bolster antitumor responses, and NKR-based approaches to amplify cytotoxic function. Additionally, adoptive T cell therapies, such as chimeric antigen receptor (CAR)-T cells, are incorporating these innate signaling components to overcome tumor-mediated immunosuppression, enhance functional longevity, and improve therapeutic efficacy. This review discusses the progress made to characterize the role of T cell intrinsic PRR activity in shaping T cell functions and highlights recent advancements in that leverage innate receptor signaling to enhance the efficacy of cancer immunotherapies.